PRAISE FOR THE LEADERSHIP CRASH COURSE - PAUL TAFFINDER (Great Britain, 2006)
To understand the difference between managing and leading people. To assess your own preference for either managing or leading. To understand why leadership is so important and valued today. To learn how leadership is different in the new globally connected business environment. To be clear on how to take the six modules of the Leadership Crash Course.